Power Quality Enhancement Using the Interline Power Flow Controller - Ben Slimane Abdelkader; Chelleli Benachiba (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
Interline Power Flow Controller (IPFC) is one of the latest generation Flexible AC Transmission system (FACTS). It is able to control simultaneously the power flow of multiple transmission lines. This paper presents a study of the impact the IPFC on profile of voltage, real and reactive power flow in transmission line in power system. The obtained results are interesting.